182k views
0 votes
Jerry is solving the equation 6(9x−10)+2(18−3x)=−8.

Step1: 6(9x)+6(−10)+2(18)+2(−3x)=−8

Step2: 54x−60+36−6x=−8

Which statement best describes the next step that Jerry can use to solve this equation?



Question 2 options:

Subtract 60 from both sides.


Add -60 and 36.


Add 6x to 54x.


Add -8 and -60.

User Thecardkid
by
5.0k points

1 Answer

5 votes

Answer:

Add -60 and 36.

Explanation:

6(9x − 10) + 2(18 − 3x) = −8

use the distributive property a(b + c) = ab + ac

6(9x) + 6(-10) + 2(18) + 2(-3x) = -8

54x - 60 + 36 - 6x = -8 combine like terms

(54x - 6x) + (-60 + 36) = -8 Answer: Add -60 and 36

48x - 24 = -8 add 24 to both sides

48x = 16 divide both sides by 48

x = 16/48

x = 1/3

User Bytech
by
4.7k points